The effects of two types of renin-angiotensin system inhibitors on the hypertension induced by new pressor protein associated with beta-factor XIIa in rats - Akbar Pejhan; Ali Gohari; Mohammad Hassan Rakhshani; Peter C Papageorgiou; Muhammad Ibrar Mustafa; Rahim Golmohammadi (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: New pressor protein (NPP) is a human plasma enzyme, which is structurally related to the beta-fragment of activated factor XII. The present study aimed to compare the effects of angiotensin converting enzyme inhibitors (captopril) and angiotensin type 1 receptor blocker (losartan) on the hypertension induced by NPP injection in normal (sham-2NX) and bilaterally nephrectomized rats (2NX). Experimental approach: In total, 60 male Wistar rats were sham operated or bilaterally nephrectomized under anesthesia. After 24 h of anesthesia with Inactin® (100 mg/kg), their systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR) were measured before and after the intravenous administration of captopril, losartan, and NPP. Findings / Results: In the sham-2NX group, after NPP injection, changes were observed in SBP (145.99 ± 3.6 mmHg), DBP (93.9 ± 3.87 mmHg), and HR (400.29 ± 12.78 bpm). In the captopril group, SBP and DBP had no significant changes, while HR increased significantly (P = 0.001). In the losartan group, SBP and DBP decreased (P = 0.001 and P = 0.000, respectively), while HR had no significant changes. In the 2NX group, after NPP injection,changes were denoted in SBP (127.89 ± 9.03 mmHg), DBP (65.86 ± 5.69 mmHg), and HR (333.35 ± 11.47 bpm). In addition, captopril injection increased DBP(P = 0.016) and HR (P = 0.036) in response to NPP injection, while losartan injection had no significant effects in this regard. Conclusion and implications: It could be concluded that losartan could improve hypertension in normal rats, while captopril deteriorated hypertension in bilaterally nephrectomized rats in this hypertension model.